Spiritual Warfare in the African Context - Asamoah-Gyadu, J. Kwabena (Lausanne Global Analyses, 2020)
In spiritual warfare, believers exercise their authority in Christ over supernatural evil which is believed to impede human progress and flourishing. This article explores the intersection between spiritual warfare and Christian mission from an African perspective. Mystical causality beliefs In the African context, generally, there is a strong belief in mystical causality, the worldview on…
free